Tanggung Jawab Inspektorat dalam Pengawasan Pengelolaan Bumdes yang Bermasalah Ditinjau dari Perspektif Hukum Pidana - Santy Ali; Ibrahim Ahmad; Robby Waluyo Amu (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This research adopts a normative juridical approach, focusing on legal norms, doctrines, and principles related to the Inspectorate's responsibility in supervising problematic BUMDes management from a criminal law perspective. Supervisory planning begins with the Regional Inspectorate preparing an Annual Supervisory Work Plan (RKPT), which outlines oversight activities for the year. Internal supervision and criminal law serve different but complementary roles: the former is preventive, aiming to detect irregularities early, while the latter is repressive, addressing legal violations. The synergy between both mechanisms is essential for transparent and efficient BUMDes financial management. Strengthening the Inspectorate’s role requires improving its institutional capacity and enhancing the competence of its personnel. This includes developing technical auditing skills and a deep understanding of criminal law related to village fund misuse. Professional auditors with legal insight are crucial for early detection of fund misappropriation, thereby fostering integrity and accountability in village financial governance.